Multigenre Projects: A Better Alternative to Teaching Research - Neuman, Stefanie (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2018)
Research and research reporting skills are an essential part of learning in and beyond school. While most teachers recognize the importance of teaching research, traditional research teaching methods are less effective than they might be. Multigenre research projects offer a more authentic and engaging way of teaching research in the classroom. Using a variety of writing genres as tools, students are able to create layers of meaning in writing and unite multiple genre artifacts to build a holistic and real-world model of information found in research. This project-based approach gives students the opportunity to use critical thinking and inquiry skills in order to problem solve their way through high-level thinking challenges. The multigenre project’s authentic and challenging nature make it a more effective model than traditional methods for teaching research in the classroom.